Influência da época de plantio na produção de cultivares e híbridos de manjericão - Pinto, Jéssika Andreza Oliveira (2017)
Basil (Ocimum basilicum L.) is a medicinal, aromatic and spicy species, consumed in the country and in the world. Faced with the need for information on basil varieties and essential oil production, the present work has the objective of evaluating the influence of the planting season on the production of cultivars and hybrids of basil. The experiments were conducted in a randomized block design, with three replications. Twenty-four basil genotypes were evaluated, with 20 commercial cultivars and four hybrids in two dry planting seasons (oct.-dec./2015), and rainy season (apr.-jun/2016). The trials were conducted at the Experimental Farm “Campus Rural da UFS”. Essential oils plants were obtained by hydrodistillation and analyzed by GC/MS-FID. The evaluated variables were: plant height, canopy width, leaf dry mass, yield and essential oil content; and contents its main constituents.The data of each period were submitted to analysis of variance and the means were grouped by theScott-Knott (p≤0,05). The analysis of individual and joint variance was performed for the experiments of the two seasons. Theparameters were estimatedgenetic variation (CVg), environmental variance (CVe), coefficient of heritability (h2) and CVg/CVe ratio. Leaf dry weight values per plant ranged from 6.23 to 75.00 g plant-1 (dry season) and 9.17 to 26.49 g plant-1 (rainy season). The hybrid Cinnamon x Maria Bonita (1.50 mL plant-1) and the cultivar Mrs. Burns (1.44 mL plant-1) presented higher yields of essential oil in the dry season. The essential oil content ranged from 0.66 to 3.21% in the dry season and from 0.80 to 4.20% in the rainy season. As for the compounds found, the majorities among the genotypes were: linalool, methyl chavicol, neral, geranial, eugenol, and (E)-methyl cinnamate, defining the formation of five groups in each epoch, with: methyl chavicol methyl chavicol (Cluster 1), citral (neral + geranial) (Cluster 2), methyl cinnamate (Cluster 3), linalool (Cluster 4), intermediate linalool (Cluster 5). All evaluated variables showed high heritability (h2) (> 70%) and CVg/CVe ratio (> 1.0), in both seasons, indicating a favorable situation for selection in a breeding program. The season influenced the production and chemical composition of essential oil of basil.